Bounds Testing Approaches to Housing Demand in Turkey: Is There a Real Estate Bubble? - Solak, Ali Osman; Kabadayı, Burhan (International Journal of Economics and Financial Issues, 2016)
In this study, housing demand in Turkey was examined with Bounds Testing Approaches for the period of 1964-2014. The total square meters of houses sold was taken as housing demand. The explanatory variables of the study are the real price of one square meter of housing, real income level, and urban population. Firstly, stationary properties of the series were checked by unit root tests, then co-integration was investigated. Lastly, we ran the Autoregressive lag model process. We found that Turkey is more sensitive to income level and there is positive relationship between prices and housing demand. This might be accounted for by the fact that houses are kinds of investment goods in Turkey. Keywords: Housing Demand, Real Estate Bubble, Bounds Testing Approach JEL Classifications: D12, D22, J11